Designing Islamic Values Integration into Sociology Learning - Tatang Hidayat; Ahmad Syamsu Rizal; Aam Abdussalam; Ahmad Ghiyats Fawwaz (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2020)
The effort to integrate Islamic values into learning has both attracted Islamic scholars to discuss and led them to offer their models which are open to examine. The purpose of this study is to discover a hypothetical model of integration planning of Islamic values into learning sociology at SMA (Sekolah Menengah Atas/Senior High School) PGII (Persatuan Guru Islam Indonesia/The Association of Indonesian Islamic Teachers) 2 Bandung. This present study employed a qualitative approach and a descriptive method in the form of case study. The data were collected using techniques namely: interviews, observation, and study documentation. The data were analysed through several steps namely: reducing, coding, displaying, interpreting of findings, and conclusion drawing. Based on the results of the study, the planning of the integration of Islamic values in learning sociology at SMA PGII 2 Bandung was applied through the use of the 2013 curriculum instrument. This integration occurred in the level of justification models. This is to say that the Quran was used as a justification tool for the learning contents of sociology learning. In this regard, the monotheism paradigm was brought into existence in the learning phases namely beginning, middle, and end of learning. Those phases served as efforts to create a religious atmosphere so that were designed and planned in order to reach Islamic values integration in sociology learning.